Restoring Oslerian clinical training in place of Flexnerian reductionism in medical education: A historical perspective - Ayesha Fatima, Manoj Chakravarty*, Nasir Abdul Latif Sarwani, Henry James, Mohamed Yasin AlTabban, Hala Ebrahim A.Aziz AlMehza (Innovative Journal of Medical and Health Sciences, 2019)
This paper addresses the historical transformation of traditional medical education resulting from application of recommendations of Abraham Flexner?s seminal report of 1910 with the incorporation of a predominantly reductionist science into the medical curriculum, and assesses the resulting systematic de-emphasis of Sir William Osler?s vision of medical students being primarily trained at the bedside of the patient. William Osler was possibly the best combination of a dedicated physician, exemplary teacher and author amalgamated into a versatile and exceptional personality. In comparison, Abraham Flexner?s lack of medical training and obsession with the laboratory nurtured by the German proclivity towards research, served to transform traditional medical education by selectively projecting scientific reductionism at the cost of the natural and existing reality of holism of the human as a living and functioning entity both in states of health and disease. This paper reinforces the concept that Oslerian bedside training should once again form the mainstay of medical education rather than the Flexnerian curricular prioritization with reductionist science and that the step would restore the primacy of clinical bedside training to its historical glory, reconfigure medical education and rejuvenate it towards the fundamental ethos of skillful competence, and simultaneously offer the best form of respect that dedicated medical teachers and physicians can pay as homage to the excellence and exceptionalism of Sir William Osler on the hundredth anniversary of his death. Key words: William Osler–Abraham Flexner–Reductionist medicine–Medical education–Medical curriculum.